Crystallization of the Lys49 PLA(2) homologue, myotoxin II, from the venom of Atropoides nummifer - Watanabe, L.; Gava, L. M.; Angulo, Y.; Lomonte, B.; Arni, R. K. (Elsevier B.V., 2004)
Myotoxin H, a Lys49 catalytically inactive phospholipase A(2) homologue from Atropoides nummifer venom, was purified, characterized and crystallized. The crystals belongs to the tetragonal system, space group P4(3)2(1)2, with unit cell parameters (a=b=68.66 and c=63.87 Angstrom). Diffraction data were collected to a resolution of 2.32 Angstrom. The crystal structure is currently being determined using molecular replacement techniques. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: myotoxin; snake venom; phospholipase A(2); Lysine-49; X-ray diffraction